2020
DOI: 10.32598/jrh.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Health in First to Sixth Economic, Social, and Cultural Development Plans of Iran: A Document Analysis

Abstract: Background: Development plans aimed at macro-management planning in a country significantly impact all functional fields. This study investigated the status and significance of the health sector in the first to sixth economic, social, and cultural development plans in Iran. Methods: This was a review study using documentary analysis method. The review was conducted with an emphasis on purposefully selected upstream information. Then, the obtained data were analyzed by the secondhand documents, including authen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The 6th 5-year National Plan of Economic, Social and Cultural Development of Islamic Republic of Iran (2017–2021) prioritizes the health of the population by expanding health service coverage and increasing financial protection mechanisms [ 4 ]. Achieving and sustaining UHC of HTN requires assessing the longer-term costs of health care, which is highly dependent on the HTN indicators such as prevalence, awareness, treatment, and control.…”
Section: Introductionmentioning
confidence: 99%
“…The 6th 5-year National Plan of Economic, Social and Cultural Development of Islamic Republic of Iran (2017–2021) prioritizes the health of the population by expanding health service coverage and increasing financial protection mechanisms [ 4 ]. Achieving and sustaining UHC of HTN requires assessing the longer-term costs of health care, which is highly dependent on the HTN indicators such as prevalence, awareness, treatment, and control.…”
Section: Introductionmentioning
confidence: 99%
“…(Document 15) This program aims to provide support, help with personal health issues, and enhance the quality of patient care and public safety by promoting health and wellbeing for the medical profession that cares for all Iran (Document 1). This shift has caused tension in the government because it has traditionally adopted a physical development model of state-run healthcare facilities for distributive justice, where its main task involves equity in access to health services (Khodayari-Zarnaq et al 2020). A former senior health official stated:…”
Section: Resultsmentioning
confidence: 99%
“…The government promotes its notion of rural FPP to serve ideological purposes, including outreach to the poor and social justice (first theme) by defining it as a facilitator of patient transfer to urban care centers to compensate for the rural health deficit alignment with the urban-oriented medical curriculum (second theme). Therefore, it is clear that failure to achieve the expected results in providing more resources, improving health outcomes and a larger health workforce and repeating the same text in the following plan indicate the government's poor commitment to some plan aspects provision, especially at a particular time (see Michielsen et al 2011;Khodayari-Zarnaq et al 2020). Beyond primary care goals, political attention to developing a specific format of the program to fill the gap between urban and rural areas in access to services along with patient transfer to care centers in cities to compensate for deficits have created an inferior discourse that shape health professionals' thoughts and decisions in relation to working and living conditions in rural areas (Document 23).…”
Section: The Rural Fpp To Represent Discipline Perceptions About Rural Communities Rural Life and Rural Residents/the Discourse Of Rural mentioning
confidence: 99%
“…The quality of the health service at the point of care in 5YPFDs also did not persist. [ 73 74 75 ] This issue could be a sign of political unwillingness because it occasionally addresses the quality of the health service at the point of care depending on the prevailing opinion of experts. The results of a study showed that whenever senior management within the health system of Iran changes, different strategies are then established and followed.…”
Section: Discussionmentioning
confidence: 99%